Asthma COPD overlap: Insights into cellular and molecular mechanisms. (June 2022) - Morissette, Mathieu; Godbout, Krystelle; Côté, Andréanne; Boulet, Louis-Philippe
Abstract: Although there is still no consensus on the definition of Asthma-COPD Overlap (ACO), it is generally accepted that some patients with airway disease have features of both asthma and COPD. Just as its constituents, ACO consists of different phenotypes, possibly depending on the predominance of the underlying asthma or COPD-associated pathophysiological mechanisms. The clinical picture is influenced by the development of airway inflammatory processes either eosinophilic, neutrophilic or mixed, in addition to glandular changes leading to mucus hypersecretion and a variety of other airway structural changes. Although animal models have exposed how smoking-related changes can interact with those observed in asthma, much remains to be known about their interactions in humans and the additional modulating effects of environmental exposures. There is currently no solid evidence to establish the optimal treatment of ACO but it should understandably include an avoidance of environmental triggers such as smoking and relevant allergens. The recognition and targeting of "treatable traits" following phenotyping is a pragmatic approach to select the optimal pharmacological treatment for ACO, although an association of inhaled corticosteroids and bronchodilators is always required in these patients. This association acts both as an anti-inflammatory treatment for the asthma component and as a functional antagonist for the airway remodeling features. Research should be promoted on well phenotyped subgroups of ACO patients to determine their optimal management. Highlights: The term 'asthma-COPD overlap' is used to describe patients with persistent airflow limitation as well as clinical features of both asthma and COPD. Patients with ACO may present as several different clinical phenotypes dictated by the predominant asthma or COPD features. ACO is the consequence of long-term interactions between asthma- and COPD-driving pathological processes. Phenotyping and targeting treatable traits is mandatory to improve management of ACO.